Penerapan Akuntansi dengan Aplikasi Buku Warung pada Usaha Mikro Kecil dan Menegah (UMKM): Studi Kasus pada Warung Lontong Bu Wardah - Azmi Lubis, Muhammad; Syahbudi, Muhammad; Syarvina, Wahyu (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The application of accounting in Micro, Small, and Medium Enterprises (MSMEs) is crucial for business sustainability and improved decision-making. This study analyzes the application of accounting at Warung Lontong Bu Wardah, a culinary MSME, using a case study method and a qualitative approach. Data were obtained through interviews and direct observation of the financial recording process carried out by the business owner. The results show that the financial recording is still manual and simple, focusing on daily cash flow without structured financial reports. This system is considered sufficient for short-term needs, but there are shortcomings in the accuracy and completeness of financial information that have the potential to affect business decision-making. This study recommends the use of a simple technology-based accounting system, such as a financial recording application, to improve efficiency, accuracy, and ease in preparing more structured and reliable financial reports for MSME owners.